Embryologic Association of Tornwaldt's Cyst with Cerebral Artery Abnormalities and Infarction: A Case Report - Michael F. Osborn; Benjamin K. Buchanan; Nassim Akle; Ahmed Badr; Jun Zhang (Case Reports in Pediatrics)
Background and Purpose. Tornwaldt's cysts are rare nasopharyngeal lesions that develop from remnants of the embryonic notochord. Summary of Case. We reported a twelve-year-old female stroke patient with Tornwaldt's cysts, whose father also suffered a stroke at age fifty two with the presence of an abdominal aortic aneurysm, suggesting a genetic influence in this case. Conclusions. This paper suggests an etiologic connection between Tornwaldt's cysts and cerebral vasculature abnormalities by way of notochordal dysfunction during development, likely the result of perturbation of notochord-derived molecular cues during development or biogenesis.